PENILAIAN GURU TK TENTANG KEPEMIMPINAN VISIONER KEPALA SEKOLAH TK DI KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU - Apriyani Manalu Apriyani Manalu; Wusono Indarto Wusono Indarto; Hukmi Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrck: The aim of the research is to find out kindergarten teachers’ assesment of visionary leadership of kindergarten principal in sub-district Payung sekaki, Pekanbaru. The population and sample of the research are all kindergarten teachers in sub-district Payung Sekaki which consist of 74 teachers. The technique of collecting the data is using Likert scale questionnaire. The tools used in analyzing the data are likert scale and statistical analysis by SPSS program for windows ver 16. In analyzing the data, the formula of percentage is applide. The result of the research revealed that from each indicator. 62,41% of visionary leadership of kindergarten principal in sub-district Payung Sekaki, Pekanbaru, is on unfavorabel category level, category 65,6% for the ability to explain the vision to the others is on both category level ,category 61,7% for the ability to communicate the vision from behavior is on unfavorabel category level ,category 60,5% for the abiliy to broaden the vision in the context of leadership is on unfavorabel category level.Key Words: Visionary Leadership